The effect of FSP on the friction and wear behaviour of Al5083 under normal atmosphere and vacuum conditions. Issue 7 (3rd May 2023) - Kara, L.
Abstract : In current technology, there are a lot of machines that work under vacuum conditions such as in space and aviation. For this reason, friction and wear properties of especially light metals, such as aluminium and magnesium alloys, which are candidates to be used in such areas should be examined under vacuum conditions. In this study, the effect of friction stir processing parameters such as traverse speed and pass number on the microstructure, hardness and wear properties of the Al 5083 alloy were investigated. During the friction stir processing, three traverse speeds and from 1 to 4 passes were applied to the surface of the samples. The wear behaviour of the processed and unprocessed samples was investigated by using the ball-on disc tribometer under air and 5 × 10 −3 mbar vacuum conditions. After friction and wear experiments, all FSPed samples showed lesser wear amount under vacuum conditions compared with air conditions.